Hedonic hunger and eating behavior after low-carbohydrate versus low-fat diets in females with lipedema and obesity - Lundanes, Julianne; Naustvoll, Thea Gustad; Tangvik, Randi J.; Martins, Catia; Nymo, Siren (Frontiers in Nutrition, 2025)
IntroductionLipedema is a chronic female disease, characterized by an excessive accumulation of subcutaneous adipose tissue in the limbs and is commonly mistaken for obesity, although the two conditions often coexist. Obesity is associated with increased hedonic hunger and dysfunctional eating behavior. However, these aspects have not been investigated in females with lipedema and obesity.ObjectivesThe objective of this secondary analysis from a randomized controlled trial was to compare changes in hedonic hunger and eating behavior following two different low-energy diets, low-carbohydrate (CHO) or low-fat, in females with lipedema and obesity.MethodsFemales with lipedema and obesity (body mass index (BMI) 30–45 kg/m2) were randomized to two different low-energy diets (1,200 kcal), low-CHO diet (LCD) (75 g CHO) or low-fat diet (180 g CHO) for 8 weeks. Hedonic hunger was assessed using the power of food scale (PFS) and eating behavior was assessed using the Dutch Eating Behavior Questionnaire (DEBQ) pre- and post-intervention.ResultsA total of 70 females were included with a mean age of 47 years, and a BMI of 37 kg/m2. The LCD group reported a reduction in Food Present (p < 0.001) and in Aggregated Score (p = 0.035) from the PFS, while no changes were seen in the low-fat diet group, with changes in Food Present over time being significantly different between groups (p = 0.050). The low-fat diet group reported increases in Restrained Eating from the DEBQ (p = 0.036) while only the LCD group reported decreases in Diffuse Emotions (p = 0.040), however, no differences between groups were found.ConclusionA LCD may induce more favorable changes in hedonic hunger and eating behavior than an isocaloric low-fat diet in females with lipedema, which may be related to altered metabolic signaling pathways related to satiety and reward.